Zwitterionic Polymer‐Coated Ultrasmall Superparamagnetic Iron Oxide Nanoparticles with Low Protein Interaction and High Biocompatibility. Issue 10 (15th September 2016) - Pombo‐García, Karina; Weiss, Stephan; Zarschler, Kristof; Ang, Ching‐Seng; Hübner, René; Pufe, Johanna; Meister, Sebastian; Seidel, Jürgen; Pietzsch, Jens; Spiccia, Leone; Stephan, Holger; Graham, Bim
Abstract: We report the synthesis and detailed in vitro evaluation of zwitterionic ultrasmall superparamagnetic iron oxide NPs (USPIONs) comprising oleic acid/oleyl alcohol‐stabilized magnetite particles (5 nm core diameter) coated with an amphiphilic zwitterionic polymer, poly(maleic anhydride‐alt‐1‐decene) substituted with 3‐(dimethylamino)propylamine (PMAL). These particles display a near‐neutral zeta potential at pH≥7 and possess high colloidal stability, maintaining a hydrodynamic diameter of ca. 15–20 nm over a wide range of pHs (4–10) and ionic strength (up to 1 m NaCl). They exhibit very low levels of nonspecific protein binding upon exposure to serum, and negligible uptake by phagocytic and non‐phagocytic hepatocarcinoma cells, which suggests that they may be able to resist rapid accumulation in the liver and spleen, a common in vivo fate for NPs. The PMAL‐USPIONs exhibit very low cytotoxicity and do not elicit an inflammatory response or display hemolytic activity in vitro. Minimal nonspecific uptake by either cancerous or non‐cancerous cell lines was observed, an important precondition to achieve highly selective targeting upon further functionalization with an active targeting agent (e.g., antibody or peptide). Overall, this study establishes the considerable potential of PMAL‐USPIONs as a platform for the future development of "stealth" NP‐based imaging and/or therapeutic agents. Abstract : Non‐stick coating : Ultrasmall superparamagnetic iron oxide nanoparticles coated with a zwitterionic, amphiphilic polymer exhibit excellent colloidal stability, high resistance to protein corona formation, minimal cytotoxicity and very low levels of cellular uptake. Moreover, they do not elicit an inflammatory cytokine response or exhibit hemolytic activity in vitro, thereby representing a promising platform for development of "stealth" imaging/therapeutic agents.